SAT0114 Synovial B cell infiltration in relationship to diagnosis and outcome in early arthritis according to the 2010 ACR/EULAR classification criteria. (23rd January 2014) - Bugatti, S.; Manzo, A.; Benaglio, F.; Vitolo, B.; Caporali, R.; Montecucco, C.
Abstract : Background: The degree of B lymphocyte infiltration in the synovial membrane is highly variable among patients with inflammatory arthritides (1). Whether qualitative and quantitative heterogeneity in B cell infiltration correlates with specific diagnoses, clinical phenotypes and disease outcomes is currently poorly determined. In particular, no previous studies have addressed the diagnostic and prognostic value of B cell synovitis according to the newly developed ACR/EULAR classification criteria for rheumatoid arthritis (RA) (2). Objectives: To explore prospectively the pattern of synovial B cell infiltration in relationship to definitive diagnosis of RA and development of persistent arthritis. Methods: Synovial tissue was obtained through ultrasound-guided biopsy (3) from an actively inflamed knee joint in 41 consecutive patients referring for diagnostic evaluation of inflammatory arthritis of <12 months duration. At the time of presentation, all patients were classified with a clinical diagnosis based on established criteria. In patients diagnosed with RA or undifferentiated arthritis (UA) according to the 2010 ACR/EULAR criteria, the need to start methotrexate (MTX) treatment within the first 6 months of follow-up was used as outcome measure. Tissue samples were analysed by immunohistochemistry. Synovial B cell infiltration was scored 0-3 based on the size and density distribution of CD20+ B cell aggregates. Results: At the time of presentation, 20 patients fulfilled the 2010 ACR/EULAR criteria for the classification of RA, 5 patients the CASPAR criteria for psoriatic arthritis and 2 patients had crystal arthropathy. The remaining 14 patients were classified as UA. After excluding definite diagnoses other than RA, patients achieving a total score ≥6 in the 2010 ACR/EULAR criteria showed increased scores for synovial B cell infiltration (1.3±1.2 vs 0.6±0.9), although the difference did not reach statistical significance (p=0.08). Among the individual domains of the 2010 ACR/EULAR criteria, the synovial B cell score significantly correlated with the score for joint involvement (rho 0.35, p=0.04). Using ROC curve analysis, a B cell score ≥2 (corresponding to the presence of large, grade 3 B cell aggregates) correctly predicted the need of MTX institution in 70% of the cases with a PPV of 100%, independent of the fulfillment of the 2010 ACR/EULAR criteria. Conclusions: The highest degrees of synovial B cell infiltration and aggregation are most frequently observed in patients with polyarticular disease who are at need for MTX initiation. Although larger prospective studies are awaited in order to validate these finding, our preliminary study suggests that the assessment of specific histopathologic features can contribute to the prognostic definition of inflammatory arthritides. References: Bugatti S, Manzo A, Bombardieri M, et al. Curr Rheumatol Rep 2011;13:440-8. Aletaha D, Neogi T, Silman AJ, et al. Arthritis Rheum 2010;62:2569-81. Scirè CA, Epis O, Codullo V, et al. Arthritis Res Ther 2007;9:R101. Disclosure of Interest: None Declared